The woolly monkey mysteries : the quest to save a rainforest species - Markle, Sandra (Sandra Markle's science discoveries, 2019)
Readers will learn how scientists use camera-trap technology to study woolly monkeys in the Manu Biosphere Reserve. These camera traps helped scientists discover information about the woolly monkeys' diet, behavior, and habitat. Known as the rainforest's gardeners, their activities and behaviors are essential to the survival of the trees and animals in the rainforest. Scientists must learn more to save this keystone species and protect the rainforests.